Respuestas
Respuesta dada por:
1
Hola! :)
Lo que haremos será hacer un pequeño cambio de variable u = x + 1 => x = u -1
![\boxed{x + 1} = 12x + 3 \\ \\ \boxed{u} = 12(u - 1) + 3 \\ \\ \boxed{u} = 12u - 9 \boxed{x + 1} = 12x + 3 \\ \\ \boxed{u} = 12(u - 1) + 3 \\ \\ \boxed{u} = 12u - 9](https://tex.z-dn.net/?f=%5Cboxed%7Bx+%2B+1%7D+%3D+12x+%2B+3+%5C%5C++%5C%5C+%5Cboxed%7Bu%7D+%3D+12%28u+-+1%29+%2B+3+%5C%5C++%5C%5C+%5Cboxed%7Bu%7D+%3D+12u+-+9)
Ya con eso calcularemos M
![M = \boxed{5} \\ \\ M = 12(5) - 9 \\ \\ M = 51 M = \boxed{5} \\ \\ M = 12(5) - 9 \\ \\ M = 51](https://tex.z-dn.net/?f=+M++%3D+%5Cboxed%7B5%7D+%5C%5C++%5C%5C+M+%3D+12%285%29+-+9+%5C%5C++%5C%5C+M+%3D+51)
Lo que haremos será hacer un pequeño cambio de variable u = x + 1 => x = u -1
Ya con eso calcularemos M
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años